2004
DOI: 10.1021/ic035484p
|View full text |Cite
|
Sign up to set email alerts
|

EDTA and Mixed-Ligand Complexes of Tetravalent and Trivalent Plutonium

Abstract: EDTA forms stable complexes with plutonium that are integral to nuclear material processing, radionuclide decontamination, and the potentially enhanced transport of environmental contamination. To characterize the aqueous Pu(4+/3+)EDTA species formed under the wide range of conditions of these processes, potentiometry, spectrophotometry, and cyclic voltammetry were used to measure solution equilibria. The results reveal new EDTA and mixed-ligand complexes and provide more accurate stability constants for previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
57
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 30 publications
(47 reference statements)
5
57
1
Order By: Relevance
“…[13][14][15][16] However, few studies have observed the formation of ternary complexes of the actinides or lanthanides with carbonate. 17 Actinide complexes of EDTA 4-can be soluble at both acidic and alkaline pHs, and may be used as a model to understand the migration and speciation of radionuclides in the environment, as well as the behaviour of actinides in various effluents and matrices. 18 Carbonate is an environmentally important and ubiquitous ligand, being found in ground and surface waters at concentrations between 10 -2 M to 10 -5 M. 19 The carbonate ion forms strong ionic interactions, due to its bidentate oxygen donors, with cations of the felements.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] However, few studies have observed the formation of ternary complexes of the actinides or lanthanides with carbonate. 17 Actinide complexes of EDTA 4-can be soluble at both acidic and alkaline pHs, and may be used as a model to understand the migration and speciation of radionuclides in the environment, as well as the behaviour of actinides in various effluents and matrices. 18 Carbonate is an environmentally important and ubiquitous ligand, being found in ground and surface waters at concentrations between 10 -2 M to 10 -5 M. 19 The carbonate ion forms strong ionic interactions, due to its bidentate oxygen donors, with cations of the felements.…”
Section: Introductionmentioning
confidence: 99%
“…Protochelin is also associated with the specific rejection of toxic W (Wichard et al 2008), and the ability to form complexes with many metals coupled with selectivity of the uptake may function as a detoxification mechanism to exclude toxic metals (Kraepiel et al 2009). Coupled with a growing body of work that has explored the geochemistry and biology of non-ferric metal interactions with other siderophores (Duckworth et al 2008b;Duckworth and Sposito 2005;Parker et al 2004Parker et al , 2007Boukhalfa et al 2004Boukhalfa et al , 2007Neu et al 2005;Harris et al 2007;Mishra et al 2009;Dahlheimer et al 2007;Frazier et al 2005;Szabo and Farkas 2011), work with protochelin has led to the suggestion that siderophores may be involved with the Fig. 1 Structures of the catecholate siderophores enterobactin, petrobactin, azotochelin, aminochelin, and protochelin transport of non-ferric metals (Kraepiel et al 2009) and have a diverse chemistry with a variety of environmentally relevant metals (Duckworth et al 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…9). These data suggest that the binding strength of the siderophore is near the binding strength of EDTA, which has a formation constant with Pu(IV) of log b = 26.44 (Boukhalfa et al 2004). The stoichiometry of the Fe (III) complex was also verified by obtaining mass spectra of the Fe-siderophore species.…”
Section: Metal-bindingmentioning
confidence: 75%